EMPOWERING GEN Z: ENHANCING ENGLISH SPEAKING SKILLS THROUGH TECHNOLOGY AND AUTHENTIC COMMUNICATION - Sumartono Sumartono (NextGen Education Review Journal, 2023)
This research article explores effective strategies to enhance English speaking skills among Generation Z (Gen Z) learners, known as the first truly digital-native generation. Despite their extensive exposure to English media, many Gen Z individuals face challenges in developing their English speaking proficiency. This mixed-methods study employs surveys and qualitative interviews to collect data on the perceived effectiveness of various strategies. The findings highlight the crucial role of technology in English speaking development, with digital language learning applications and online language exchange platforms being recognized as potent tools. Moreover, the study emphasizes the significance of authentic communication experiences, such as role-plays and debates, and the value of peer collaboration in improving English speaking skills. Common challenges identified include time constraints and the influence of informal language use. Consequently, the implications of this research underscore the integration of technology, the promotion of authentic communication, the facilitation of peer collaboration, and the implementation of strategies to address time constraints in English language instruction for Gen Z learners. By adopting these approaches, educators and policymakers can establish engaging learning environments that empower Gen Z learners to thrive in our interconnected society.